2021
DOI: 10.1007/s11356-021-17786-8
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette heavy smoking alters DNA methylation patterns and gene transcription levels in humans spermatozoa

Abstract: Tobacco smoking is considered the most common reason of death and infertility around the world. This study was designed to assess the impact of tobacco heavy smoking on sperm DNA methylation patterns and to determine whether the transcription level of ALDH3B2, PTGIR, PRICKLE2, and ALS2CR12 genes is different in heavy smokers compared to non-smokers. As a screening study, the 450 K array was used to assess the alteration in DNA methylation patterns between heavy smokers (n = 15) and non-smokers (n = 15). Then, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Other studies demonstrated a significant decline in the transcription level of PRM1 and PRM2 in smokers spermatozoa compared to non-smokers [36], and that reactive oxygen species (ROS) resulting from smoking might be responsible for the decrease of the transcription level of genes like IκBα [37]. Another study showed a downregulation in the transcription levels of MAPK8IP3, GAA, ANXA2, PRRC2A, and PDE11A genes in heavy smokers compared to non-smokers and an upregulation in the MAPK8Ip3, ANXA2, PRRC2A, and PDE11A transcription levels in heavy smokers compared to non-smokers [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies demonstrated a significant decline in the transcription level of PRM1 and PRM2 in smokers spermatozoa compared to non-smokers [36], and that reactive oxygen species (ROS) resulting from smoking might be responsible for the decrease of the transcription level of genes like IκBα [37]. Another study showed a downregulation in the transcription levels of MAPK8IP3, GAA, ANXA2, PRRC2A, and PDE11A genes in heavy smokers compared to non-smokers and an upregulation in the MAPK8Ip3, ANXA2, PRRC2A, and PDE11A transcription levels in heavy smokers compared to non-smokers [38].…”
Section: Discussionmentioning
confidence: 99%
“…Total sperm count, total motility, progressive motility, normal form, vitality, and sperm membrane integrity were significantly higher in non-smokers group in comparison to heavy smokers group: 52. 38…”
Section: Characteristics Of the Study Populationmentioning
confidence: 99%
“…Other studies have demonstrated a significant decline in the transcription levels of PRM1 and PRM2 in smokers’ spermatozoa compared to that of non-smokers [ 52 ], and that reactive oxygen species (ROS) resulting from smoking might be responsible for the decrease in the transcription levels of genes such as IκBα [ 53 ]. Another study showed a downregulation in the transcription levels of the MAPK8IP3 , GAA , ANXA2 , PRRC2A , and PDE11A genes in heavy smokers compared to non-smokers and an upregulation in the MAPK8Ip3 , ANXA2 , PRRC2A , and PDE11A gene transcription levels in heavy smokers compared to non-smokers [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of this phenomenon may explain the new field of epigenomic paternal transmission, which suggests that paternal exposure to environmental challenges plays a critical role in the offspring's future health and the transmission of acquired traits through generations [ 54 ]. Several studies showed that smoking alters DNA methylation patterns and gene transcription levels in human spermatozoa [ 55 , 56 ]. Paternal exposure to cigarette smoke leads to increased global methylation of sperm DNA and alterations to the differentially methylated regions of the DLK1 gene in offspring, which in turn leads to elevated liver fat accumulation and may perturb long-term metabolic function in offspring [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%